The Utilization and Management of Pemelisan Temple Area as Ritual Facilities in the Mangrove Forest of Desa Adat Sesetan, Denpasar - I Made Pria Dharsana; I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Gede Sugiartha; A. A. Sagung Laksmi Dewi (Community Service Journal of Law, 2024)
Local wisdom has positive implications for improving the economy of local communities, understanding natural and cultural phenomena, and providing support for the preservation of nature and culture itself; therefore, the Balinese tourism format, which is steeped in cultural tourism, will never fade. The cultural character and cultural heritage of Bali, which includes symbols, signs, forms of written artistic expression, language, lifestyle, ritual systems, traditional knowledge, and mythology inherited from the predecessors of the Balinese people, makes it a special attraction for the world of tourism. Pemelisan Temple, which is located in the Mangrove forest in Sesetan village, requires special attention to be developed and managed using appropriate methods for the preservation and sustainability of customs and culture in the context of implementing religious tourism and ecotourism in the Mangrove forest. With this community service program, our team would like to provide advice to the village administrators regarding arrangements for cooperation in managing the use of Mangrove forest conservation in Sesetan village and to study the development of the use of Mangrove forests for Hindu religious ritual facilities in Sesetan village